Does anti-corruption course develop anti-corruption attitude of students? The case of higher education in Jambi-Indonesia - Nisaul Fadillah; Yorina An'guna Bansa (IJER (Indonesian Journal of Educational Research), 2020)
This study evaluated the teaching of anti-corruption course by determining the relationship between the perception of students about lecturers’ teaching methods, learning outcomes, and attitudes toward corruption among bachelor students. Data were withdrawn from questionnaires distributed to 80 students in four faculties and their assessment paper and analysed with Pearson analysis. The results showed that there was no significant relationship between students' perceptions of lecturer teaching methods and attitudes towards anti-corruption (r = 0.031), there was no significant relationship between learning outcomes and attitude towards anti-corruption (r =. 003). Furthermore, regression analysis found that students' perceptions of lecturer teaching methods in the Anti-corruption Course can only predict students’ attitudes toward anti-corruption at 1%, whereas students’ learning outcomes did not affect their attitudes toward anti-corruption.